Sex-Specific Epidemiology of Heart Failure Risk and Mortality in Europe Results From the BiomarCaRE Consortium - Magnussen C.; Niiranen T.J.; Ojeda F.M.; Gianfagna F.; Blankenberg S.; Vartiainen E.; Sans S.; Pasterkamp G.; Hughes M.; Costanzo S.; Donati M.B.; Jousilahti P.; et al. (ELSEVIER SCI LTD, 2022)
OBJECTIVES: This study investigates differences between women and men in heart failure (HF) risk and mortality.
BACKGROUND: Sex differences in HF epidemiology are insufficiently understood.
METHODS: In 78,657 individuals (median 49.5 years of age; age range 24.1 to 98.7 years; 51.7% women) from community-based European studies (FINRISK, DanMONICA, Moli-sani, Northern Sweden) of the BiomarCaRE (Biomarker for Cardiovascular Risk Assessment in Europe) consortium, the association between incident HF and mortality, the relationship of cardiovascular risk factors, prevalent cardiovascular diseases, biomarkers (C-reactive protein [CRP]; N-terminal pro-B-type natriuretic peptide [NT-proBNP]) with incident HF, and their attributable risks were tested in women vs. men.
RESULTS: Over a median follow-up of 12.7 years, fewer HF cases were observed in women (n = 2,399 [5.9%]) than in men (n = 2,771 [7.3%]). HF incidence increased markedly after 60 years of age, initially with a more rapid increase in men, whereas incidence in women exceeded that of men after 85 years of age. HF onset substantially increased mortality risk in both sexes. Multivariable-adjusted Cox models showed the following sex differences for the association with incident HF: systolic blood pressure hazard ratio (HR) according to SD in women of 1.09 (95% confidence interval [CI]: 1.05 to 1.14) versus HR of 1.19 (95% CI: 1.14 to 1.24) in men; heart rate HR of 0.98 (95% CI: 0.93 to 1.03) in women versus HR of 1.09 (95% CI: 1.04 to 1.13) in men; CRP HR of 1.10 (95% CI: 1.00 to 1.20) in women versus HR of 1.32 (95% CI: 1.24 to 1.41) in men; and NT-proBNP HR of 1.54 (95% CI: 1.37 to 1.74) in women versus HR of 1.89 (95% CI: 1.75 to 2.05) in men. Population-attributable risk of all risk factors combined was 59.0% in women and 62.9% in men.
CONCLUSIONS: Women had a lower risk for HF than men. Sex differences were seen for systolic blood pressure, heart rate, CRP, and NT-proBNP, with a lower HF risk in women. (C) 2019 by the American College of Cardiology Foundation.